Effect of Soursop Leaf and Lemongrass Formulation on the Total Phenolic Content of a Herbal Brewed Tea with Powdered Honey as a Natural Sweetener - Kireina Farhah Nabila; Efri Mardawati; Selly Harnesa Putri (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2026)
Background: Functional beverages has a widely potential benefit for health due to bioactive compounds, including phenolic, serving as a natural antioxidants. Soursop leaves (Annona muricata L.) and lemongrass (Cymbopon citratus) combined with powdered honey may contain a phenolic compound potential for herbal beverages, especially the herbal brewed tea, but yet hasn’t been widely developed. Purpose: This research focused on identifying the effect of different formulations of soursop leaves and lemongrass on the total phenolic content of a herbal brewed tea with powdered honey as a natural sweetener. Method: A completely randomized design with a single factor was applied for the five different formulations, namely F1 (90:0:10), F2 (0:90:10), F3 (45:45:10), F4 (25:65:10), and F5 (65:25:10), replicated four times each. The observed variable was the total phenolic content of each herbal brewed tea formulation produced. Result: The ANOVA results showed that different formulations significantly affected the total phenolic content of herbal brewed tea (p<0.05), ranged from 2.82 to 8.06 mg GAE/g. The highest phenolic content was obtained in F5 (8.06 ± 0.34 mg GAE/g), followed by F1 (7.71 ± 0.11 mg GAE/g), F3 (5.44 ± 0.28 mg GAE/g), F4 (4.15 ± 0.36 mg GAE/g), and F2 (2.82 ± 0.19 mg GAE/g). Thus, F5 (65:25:10) was considered the most optimal formulation and had the potential to produce a suitable herbal brewed tea made from soursop leaves, lemongrass, and powdered honey.